Mit Bargeld zahlen - ein Auslaufmodell? - Hanno Beck; Aloys Prinz; Christoph Sorge; Heike Winter; Heike Wörlen; Gerhard Rösl; Franz Seitz (Wirtschaftsdienst, 2015)
Die Digitalisierung hat neben Kreditkarten auch unterschiedliche Bezahlsysteme möglich gemacht. Mittlerweile sind diese neuen Systeme auf dem Weg, das Bargeld abzulösen. Tatsächlich gibt es aus der Wissenschaft sogar Empfehlungen, das Bargeld ganz abzuschaffen. Die Autoren des Zeitgesprächs setzen sich mit den Argumenten für die Abschaffung auseinander und kommen zu dem Ergebnis, dass Bargeld wichtige Funktionen hat, auf die nicht so leicht verzichtet werden sollte. – – Digitisation has a growing effect on payment instruments, resulting in the reduction of the special status of cash. Three categories of payment types (cash, electronic payment and anonymous payment schemes) are available. Germany is one of the last countries in Europe with a high level of cash usage. Some economists have gone so far as to propose abolishing cash completely, because it supports the black economy, it helps to avoid negative interest rates and its handling is expensive and inefficient. But abolishing cash is not the silver bullet that some claim it would be. People would start turning to substitutes for cash, maybe even creating a new informal currency. This would reduce the effectiveness and efficiency of such a move, and it might even create new opportunities for criminal activities and the inflation of speculative bubbles. Moreover, if we regard privacy in monetary transactions as a social value, eliminating notes and coins as a means of payment may have serious side effects for citizens. While anonymous electronic payments are available in theory, abolishing cash would severely harm individuals' privacy in practice.
Keywords: E42; K42; 330; Bargeld; Nachfrage; Bargeldloser Zahlungsverkehr; Wirkungsanalyse